2022
DOI: 10.3390/biomedicines10092076
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Natural Steroid Sapogenin Diosgenin as a Direct Dual-Specific RORα/γ Inverse Agonist

Abstract: The steroid sapogenin diosgenin is a well-known natural product with a plethora of described pharmacological activities including the amelioration of T helper 17 (Th17)-driven pathologies. However, the exact underlying mode of action of diosgenin leading to a dampened Th17 response is still largely unknown and specific molecular targets have yet to be identified. Here, we show that diosgenin acts as a direct ligand and inverse agonist of the nuclear receptor retinoic acid receptor (RAR)-related orphan receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Additionally, Nobiletin is a natural compound that directly binds to and activates RORα, modulating circadian rhythms and showing robust in vivo efficacies to combat clock-associated pathophysiologies and age-related decline [ 59 ]. One latest study confirmed that diosgenin acted as a direct ligand and inverse agonist of RORα, which is a key transcription factor involved in Th17 cell differentiation and metabolism [ 60 ]. Another group underscored the screening of a large combinatorial library of 1,5-disubstituted acylated 2-amino-4,5-dihydroimidazoles using a demonstrated synthetic and screening approach and the utility of the positional scanning libraries strategy for the rapid identification of a novel class of RORα inhibitors.…”
Section: Rorα-related Compoundsmentioning
confidence: 99%
“…Additionally, Nobiletin is a natural compound that directly binds to and activates RORα, modulating circadian rhythms and showing robust in vivo efficacies to combat clock-associated pathophysiologies and age-related decline [ 59 ]. One latest study confirmed that diosgenin acted as a direct ligand and inverse agonist of RORα, which is a key transcription factor involved in Th17 cell differentiation and metabolism [ 60 ]. Another group underscored the screening of a large combinatorial library of 1,5-disubstituted acylated 2-amino-4,5-dihydroimidazoles using a demonstrated synthetic and screening approach and the utility of the positional scanning libraries strategy for the rapid identification of a novel class of RORα inhibitors.…”
Section: Rorα-related Compoundsmentioning
confidence: 99%
“…Diosgenin ( Figure 1E ) is a natural steroidal sapogenin ( Schwarz et al, 2022 ). Diosgenin is found in Dioscorea alata L., Smilax china L., and Trigonella foenum-graecum L. ( Jesus et al, 2016 ).…”
Section: Effect Of Natural Products On Hormones Secreted By the Adren...mentioning
confidence: 99%
“…TAN was already recognized in herbal medicine for its anti-inflammatory, antioxidant, and vascular endothelial cell-protective properties. Likewise, Schwarz et al [ 31 ] investigated the mode of action of the steroid sapogenin diosgenin, previously identified in the Chinese plant Dioscoreae rhizoma, in dampening the autoimmune inflammatory response in T helper 17 (Th17)-driven pathologies. By combining methodological approaches including gene expression analysis and in silico analyses, the authors revealed diosgenin as an inverse agonist of the key transcription factors leading to Th17 cell differentiation and metabolism.…”
mentioning
confidence: 99%